Confluence-dependent resistance to cisplatin in lung cancer cells is regulated by transforming growth factor-beta. (20th April 2016) - Yokokura, Saki; Kanaji, Nobuhiro; Tadokoro, Akira; Yokokura, Shigeyuki; Kadowaki, Norimitsu; Bandoh, Shuji
ABSTRACT: Purpose of the Study: Confluence-dependent resistance (CDR) is a phenomenon in which the efficacy of anti-cancer agents decreases when cell density increases. CDR in lung cancer has never been reported. The purpose of this study is to investigate if CDR can occur in NSCLC cells and to find a role for transforming growth factor (TGF)-β as a mechanism of CDR.Materials and Methods: Non–small cell lung cancer (NSCLC) cell lines A549 and H2228 were exposed to cisplatin in a variety of cell density conditions. RNA interference targeting TGF-β receptor I was performed to silence the TGF-β pathway.Results: CDR to cisplatin was induced in NSCLC cells, whereas CDR to crizotinib, an inhibitor of activin receptor-like kinase, was not observed. During confluent conditions, the TGF-β1 concentration in the culture medium was the highest. Exogenous TGF-β1 inhibited cell proliferation and reduced sensitivity to cisplatin. Inhibition of the TGF-β pathway increased in terms of sensitivity to cisplatin at confluency.Conclusions: CDR to cisplatin can occur in NSCLC cells, and the TGF-β pathway is associated with the regulation of CDR.